A Unified Recursive Theory of Everything (URToE): A Mathematical Framework for Fundamental and Applied Sciences - Yadav, Utkarsh (Journal of Educational Research and Policies, 2025)
This paper introduces the Unified Recursive Theory of Everything (URToE), proposing that all physical phenomena arise from a single recursive framework rather than independent forces. By redefining gravity, quantum mechanics, time, and dark matter as manifestations of recursive attractors, the study presents a novel approach to unification in physics and beyond. The proposed universal recursive equation integrates these phenomena into a single predictive model. Computational validations using TensorFlow demonstrate the convergence of fundamental forces into stable attractor states, supporting the viability of recursion as a fundamental principle of reality.